Bite me! - Francis, Melissa McKenzie (New York : HarperTeen, 2009)
AJ, a teenage vampire, hides her identity from her new stepfamily--among which is her ex-boyfriend--and investigates the secrets of her heritage.
Keywords: Vampires -- Juvenile fiction; Stepfamilies -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction